P220 Patient's disease perception and health-related quality of life with IBD: Results from a Spanish cohort with 15 years of follow up. (30th January 2023) - Elosua Gonzalez, A; Rubio, S; Irisarri, R; Campillo, A; Nantes, Ó; Vicuña, M; Angós, R; Zozaya, J M; Rodríguez, C
Abstract: Background: Crohn's Disease (CD), ulcerative colitis (UC) and IBD unclassified (IBD-U) may affect the health-related quality of life (HRQoL). We evaluated HRQoL and patient's disease course perception in the Navarra Incident Cohort (includes all new diagnosis from 2001-2003 in Navarra, Spain) Methods: All patients were invited to complete two HRQoL questionnaires: the generic EuroQoL-5 dimensions (EQ-5D-3L) and the Inflammatory Bowel Disease Questionnaire (IBDQ-36). Patients' disease course perception was evaluated using the four disease curves from the IBSEN cohort Results: From 285 patients initially diagnosed, we obtained 158 questionnaires (72% response rate after excluding deaths and lost to follow-up); 103 UC, 50 CD and 5 IBD-U, 40% women and median age 52 (22-84). Most patients were in remission (99% UC/ 88% CD/ 100% IBD-U). In EQ-5D-3L, 55% answered not having, 41% having some and 4% having significant impairment in at least one dimension. "Pain/discomfort" and "anxiety/depression" were the most affected dimensions with no differences by diagnosis. However, 91% of UC and 85% of CD patients considered their health status to be the same or better compared to the previous year. Median IBDQ-36 score in UC was significantly higher than CD (227 vs 212, p=0.04). No differences were found in partial median scores in bowel symptoms and social impairment with significantly higher median scores in UC compared to CD in systemic symptoms, emotional function and functional impairment. Similar results between UC and IBD-U were obtained (table1). Regarding disease course, 67% of UC and 54% of CD patients chose to have a progressive decrease in the intensity of symptoms since onset (p=0.2). Significantly more CD that UC patients considered a disease with recurrent flares of activity (40% vs 23%, p=0.015). The increase in symptoms throughout the evolution was the pattern chosen by 8% of UC and 4% of CD patients, while only 2% in each disease defined its situation as persistent chronic activity throughout the follow-up. Conclusion: - Patients have a significant impact in their HRQoL despite being in remission - Systemic symptoms, emotional function and functional impairment were more affected in CD patients. - Most patients considered their disease as a progressive decrease in the intensity of symptoms with significantly more CD patients considered having recurrent flares of activity.